A Case of Cephalic Tetanus in an Elderly Patient with Trismus - Marilia Bernardes; Saberio Lo Presti; Kenneth Ratzan (Case Reports in Infectious Diseases)
We report a case of a 77-year-old woman who presented to the Emergency Room with a three-day history of oral lesions and jaw tightness. Her physical examination was remarkable for the presence of trismus and white ulcers on the visible portion of the tongue. CT head and neck was unremarkable, and she was discharged with empiric treatment for oral candidiasis. She returned two days later with worsening symptoms and subsequently developed tonic-clonic seizures. MRI of the brain and temporomandibular joints were noncontributory. Psychiatry was consulted, and the patient was prescribed olanzapine and mirtazapine for suspected depression with somatization symptoms. She continued to deteriorate despite therapy and developed right lid ptosis and ophthalmoparesis, which led to a presumptive diagnosis of cephalic tetanus. On the 14th day of illness, tetanus immune globulin, metronidazole, and tetanus toxoid vaccine were administered. Despite treatment, the patient died after 24 days of hospitalization. This case illustrates the importance of early recognition of tetanus since successful treatment depends on timely administration of immune globulin.